2014
DOI: 10.1108/jarhe-02-2013-0008
|View full text |Cite
|
Sign up to set email alerts
|

Corporate governance in Kenya's public universities

Abstract: Purpose – The purpose of this paper is to explore the corporate governance practices adopted by public universities in Kenya, itself a developing country. Corporate governance practices in Africa, especially the sub-Saharan part, are weak and limited research has been done in this area. Design/methodology/approach – The researcher adopted the realism paradigm and relied on qualitative data obtained from five case study organizations. A t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 37 publications
0
1
0
1
Order By: Relevance
“…There have been widespread concerns that rapid expansion of higher education has led to a degradation of quality, particularly in the lower-income countries of Africa, Asia and Latin America as manifested variously in poor physical infrastructure, overcrowded classrooms, curricula that do not respond to market needs, academic staff without the required qualifications, or moonlighting in multiple institutions (Tilak, 2013;Altbach et al 2009;Tetty & PHEA 2009). Mulili, (2014), observed that constrained service delivery contributes to increased customer complaints which are an indicator of customer dissatisfaction. Widespread dissatisfaction of both internal and external customers affects the reputation of universities and its ability to attract and retain customers leading to poor performance (Agarwal 2009;Oketch 2016;Pitan & Adedeji 2012;McCowan et al 2017).…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…There have been widespread concerns that rapid expansion of higher education has led to a degradation of quality, particularly in the lower-income countries of Africa, Asia and Latin America as manifested variously in poor physical infrastructure, overcrowded classrooms, curricula that do not respond to market needs, academic staff without the required qualifications, or moonlighting in multiple institutions (Tilak, 2013;Altbach et al 2009;Tetty & PHEA 2009). Mulili, (2014), observed that constrained service delivery contributes to increased customer complaints which are an indicator of customer dissatisfaction. Widespread dissatisfaction of both internal and external customers affects the reputation of universities and its ability to attract and retain customers leading to poor performance (Agarwal 2009;Oketch 2016;Pitan & Adedeji 2012;McCowan et al 2017).…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…As universidades públicas têm sido submetidas a vários desafios nos últimos anos, tais como urgência de orçamento e oferta de vagas sem destinação proporcional de pessoal e A governança nas universidades públicas é um tema pouco explorado (SILVEIRA et al, 2017). A maioria dos estudos encontrados limita-se à análise e a levantamentos sobre o nível de aderência das Instituições de Ensino Superior (IES) às práticas de boa governança (SALES; PETER; MACHADO; NASCIMENTO, 2020;BARBOSA, 2019;HONG, 2018;ZORZAL, 2015;MULILI, 2014). Portanto, não buscaram identificar fatores que motivem as variações da qualidade da governança.…”
Section: Introductionunclassified